Formulation of Nanoemulsion of Gotu Kola (Centella asiatica (L.) Urban) Leaves Extract as Active Ingredients to Produce Antioxidant Facial Serum - Fitri, Noor; Tanjungsari, Afifah Adinda; Himmi, Setiawan Khoirul; Solihat, Nissa Nurfajrin (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2024)
Abstract: Free radicals can cause cell damage such as premature aging. To protect, ward off and stabilize free radicals, antioxidant compounds can be used. Plants that can be used as a source of antioxidants are gotu kola (Centella asiatica (L.) Urban). The aim of this research is formulating a nanoemulsion of gotu kola leaves extract as an active ingredient for producing the antioxidant serum. The steps of this research include: (1) extraction by maceration and Microwave-Assisted Extraction (MAE); (2) extract characterization; (3) formulation of nanoemulsion using Self-Nanoemulsifying Drug Delivery System (SNEDDS) method; (4) nanoemulsion testing: stability test, antioxidant activity test, and irritation test, (5) nanoemulsion characterization which includes particle size, transmittance, pH, and viscosity. The results showed that: (1) yields of the maceration method and MAE were 14,60% and 17,54%; (2) antioxidant compounds in gotu kola leaves extract are squalene, kaempferol, asiaticoside; The IC50 of the maceration and MAE extract were 93,152 ppm and 80,365 ppm; (3) nanoemulsions were made in 3 formulas (0,1; 0,3; and 0,5 g) with fixed variables of capryol 90, tween 20, and PEG 400 (1,5; 2,5; and 1); (4) stability test showed that only F1 was stable; the IC50 value of nanoemulsion is 2604,967 ppm; and the F1 irritation test showed no erythema and edema; (5) The particle size of F1 is 166,7 nm with a transmittance value of 97.4%, a pH of 5,33, and a viscosity of 75,35 cP.